2021
DOI: 10.3390/ijms22063097
|View full text |Cite
|
Sign up to set email alerts
|

Novel Ferrocene Derivatives Induce G0/G1 Cell Cycle Arrest and Apoptosis through the Mitochondrial Pathway in Human Hepatocellular Carcinoma

Abstract: In this study, detailed information on hepatocellular carcinoma (HCC) cells (HepG-2, SMMC-7721, and HuH-7) and normal human liver cell L02 treated by ferrocene derivatives (compounds 1, 2 and 3) is provided. The cell viability assay showed that compound 1 presented the most potent and selective anti-HCC activity. Further mechanism study indicated that the proliferation inhibition effect of compound 1 was associated with the cycle arrest at the G0/G1 phase and downregulation of cyclin D1/CDK4. Moreover, compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
0
7
0
1
Order By: Relevance
“…Furthermore, the half-maximal inhibitory concentration (IC 50 ) values in Table S1 indicated that F1 and F3 had much higher anti-cancer activity in Jurkat cells. Moreover, our previous study indicated that F1 could induce G0/G1 cell cycle arrest and apoptosis through the mitochondrial pathway in several human hepatocellular carcinoma cell lines [ 17 ]. Combined with the fact that the Jurkat cell line is extensively employed as a model of T cell signaling [ 19 ] and an appropriate model for drug investigation [ 20 ], the molecular mechanism of F1 and F3 in Jurkat cells was further studied.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the half-maximal inhibitory concentration (IC 50 ) values in Table S1 indicated that F1 and F3 had much higher anti-cancer activity in Jurkat cells. Moreover, our previous study indicated that F1 could induce G0/G1 cell cycle arrest and apoptosis through the mitochondrial pathway in several human hepatocellular carcinoma cell lines [ 17 ]. Combined with the fact that the Jurkat cell line is extensively employed as a model of T cell signaling [ 19 ] and an appropriate model for drug investigation [ 20 ], the molecular mechanism of F1 and F3 in Jurkat cells was further studied.…”
Section: Resultsmentioning
confidence: 99%
“…In the past decades, there has been increasing interest in ferrocene derivatives, especially for their anti-cancer activities. Recently, a series of 2-acyl-1-dimethylaminomethyl-ferrocenes F1–F7 have been synthesized by our group [ 18 ], and we reported that F6 selectively inhibited the proliferation of hepatocellular carcinoma cell lines through a mitochondrial pathway [ 17 ]. Herein, to continuing our interest in the bioactivity of F1–F7, their anti-cancer activities were well evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harmicene 28 , also an O-7-substituted TT-harmine derivative, had an even more pronounced effect on the HCT116 cell cycle. Furthermore, it is known that ferrocene derivatives also inhibit the proliferation of various cancer cells through the induction of G0/G1 cell cycle arrest, downregulation of cyclin D1, CDK4 [ 50 ], and CDK6 and concomitant increases in p27 and p21 expression [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…以药物化学研究 为例, 多种二茂铁衍生物已被发现具有抗菌、抗疟疾、 抗真菌以及抗病毒活性. 最近, 崔秀灵课题组 [7][8][9] 发现, 其合成的平面手性 2-酰基-二茂铁衍生物(3)在与肝癌细 胞 [10] 和 T 细胞急性淋巴细胞 [11] 等的体外实验中, 均表现 出良好的肿瘤抑制活性, 有望成为治疗上述肿瘤疾病的 潜在药物.…”
unclassified